A tale of witchcraft... - Colfer, Chris, 1990- (Little, Brown and Company, 2020)
A witch named Mistress Mara arrives at the Celeste Weatherberry Memorial Academy of Magic and begins recruiting students to her new witchcraft school, causing suspicion among Brystal and her friends. Soon the group discovers that the fragile peace they hoped for is in danger of disintegrating as the Righteous Brotherhood takes aim at Brystal to destroy all magical life in the kingdom.